The Features and Processes of Poisoning Registries: A Scoping Review: Features and processes of poisoning registries - Sabahi, Azam; Asadi, Farkhondeh; Shadnia, Shahin; Rabiei, Reza; Hosseini, Azam Sadat (International Journal of Medical Toxicology and Forensic Medicine, 2021)
Background: Poisoning is a common condition worldwide that requires precise evaluation of the quality and rapid management. Registry plays an essential role in the management of toxins. This study aimed to examine the features and processes of poisoning registries. Methods: This review study was conducted in 2020. Several searches were conducted in the following scientific databases: PubMed, Scopus, Embase, and Web of Science using a combination of keywords, such as “data management, registry, poison, and toxic”. The review of titles, abstracts, and full-text of the selected articles was independently performed by two researchers. Besides, the obtained data were analyzed based on the research objectives by the content analysis method. Results: Some critical features of registries were considered the confidentiality of patients’ information, i.e., equipped with various technologies, such as Geographical Information System (GIS), warning systems, searches, and text retrieval tools. The most common sources of case findings were self-reported contacts by individuals and healthcare professionals to poison control centers. Moreover, the main tool for data collection was electronic forms. The major indices of data quality were the accuracy, completeness, and consistency of the data. Phone calls were usually made at follow-ups. Conclusion: The registry’s features and processes are an essential and fundamental step to achieve the registry goals, as well as designing and developing these systems. It is recommended that the registries be equipped with various technologies to better manage the exposure cases. It is recommended to use educational, incentive, competitive, participatory, and motivational mechanisms among all organizations and individuals involved in poisoning registry programs.